Targeting the Type 5 Metabotropic Glutamate Receptor: A Potential Therapeutic Strategy for Neurodegenerative Diseases? - Budgett, Rebecca F.; Bakker, Geor; Sergeev, Eugenia; Bennett, Kirstie A.; Bradley, Sophie J. (Frontiers in Pharmacology, 2022)
The type 5 metabotropic glutamate receptor, mGluR5, has been proposed as a potential therapeutic target for the treatment of several neurodegenerative diseases. In preclinical neurodegenerative disease models, novel allosteric modulators have been shown to improve cognitive performance and reduce disease-related pathology. A common pathological hallmark of neurodegenerative diseases is a chronic neuroinflammatory response, involving glial cells such as astrocytes and microglia. Since mGluR5 is expressed in astrocytes, targeting this receptor could provide a potential mechanism by which neuroinflammatory processes in neurodegenerative disease may be modulated. This review will discuss current evidence that highlights the potential of mGluR5 allosteric modulators to treat neurodegenerative diseases, including Alzheimer’s disease, Huntington’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. Furthermore, this review will explore the role of mGluR5 in neuroinflammatory responses, and the potential for this G protein-coupled receptor to modulate neuroinflammation.